Hydrothermally treated coals for pulverized coal injection. [Quarterly] technical progress report, January--March 1995 - Walsh, D.E.; Rao, P.D.; Ogunsola, O.; Lin, H.K. (Alaska Univ., Fairbanks, AK (United States). School of Mineral Industry, 1995)
This project is investigating the suitability of hydrothermally dried low-rank coals for pulverized fuel injection into blast furnaces in order to reduce coke consumption. Coal samples from the Beluga coal field and the Usibelli Coal Mine, Alaska, are being used for the study. Crushed coal samples were hydrothermally treated at three temperatures, 275, 300 and 325degreesC, for residence times ranging from 10 to 120 minutes. Products are being characterized to determine their suitability for pulverized coal injection. Characterization includes proximate and ultimate analyses, vitrinite reflectance and TGA reactivity. A literature survey is being conducted.